Pengaruh Media Interaktif Terhadap Minat Belajar Siswa di SMK Negeri 1 Tengaran - Putri Thahlia; Mila Chrismawati Paseleng (Peneliti.net, 2023)
Students in computer and network expertise competence (TKJ) have good personalities, judging from their attitudes when participating in learning activities that are relatively conducive. According to information I got from several teachers, there are still students who lack focus in learning. Because approximately 2 years of learning is carried out online, students are bored and bored so that interest in learning decreases. In learning activities at SMK Negeri 1 Tengaran, especially in class X TKJ in Informatics subjects, teachers still use simple methods which still use whiteboard media to write and power points to present learning. To make learning more effective, the learning method that will be used is the Quizizz interactive media method which can be a potential alternative to increase student learning interest. This type of research uses Pretest-Posttest Control Group Design Experimental research involving 2 groups, namely the experimental group and the control group. Based on theoretical opinions and relevant research that has been explained, researchers concluded that there is an influence of quizizz interactive media on student learning interest at SMK Negeri 1 Tengaran.Based on the results of research conducted in control classes and experiments on grade X TKJ students at SMK Negeri 1 Tengaran in the subject of Informatics Data Communication and Mobile Phones material, it can be concluded that there is a visible influence on student learning interest in the eyes informatics lessons using quizizz interactive media in class X TKJ. Furthermore, learning using quizizz interactive media also has a positive impact on students' interest in informatics learning.